Current situation of comprehensive utilization of coal gangue and exploration of ways of high-value utilization:A case study of China National Coal Group Corporation - Lei ZHU; Wenzhe GU; Zhiwei HE; Chengyong LIU; Mengye ZHAO; Tianqi SONG; Yun ZHANG; Yuyi WU; Zhicheng LIU; Xinfu ZHANG; Peng ZHANG; Fengtian SHENG (Meitan kexue jishu, 2025)
In the context of the “double carbon” goal, coal is the cornerstone of national energy security, and its green development is of strategic significance to my country’s economic construction and social development. Relying on its rich coal resource reserves, China Coal plays an important role in ensuring the country’s energy supply. However, while high-yield and efficient mining of coal resources, a large amount of coal gangue is produced, causing pollution to soil, air, water and other countries. The issue of reasonable disposal and resource utilization of coal gangue has become the main bottleneck restricting the green development of mining area. The distribution characteristics, physical and chemical properties and utilization methods of coal gangue in China were investigated, the comprehensive utilization policies of coal gangue were systematically sorted out, and the use of coal gangue in power generation utilization, production of building materials, preparation of chemical products, recycling of beneficial minerals, and agriculture were elaborated. The principles and technical routes of utilization methods in aspects such as application, underground filling and land reclamation were investigated, and the application progress of coal gangue in mines belonging to China Coal was investigated. The results show that the mine is located in 20 mining areas in 8 provinces. Affected by coal mine geological conditions, mining technical conditions and washing conditions, the distribution of gangue presents the characteristics of wide range, complex structure, and diverse types; the comprehensive utilization of coal gangue in Anhui, Jiangsu, Henan and Heilongjiang regions presents the characteristics of “peripheral radiation”, and the comprehensive utilization of coal gangue in Shanxi, Shaanxi, Inner Mongolia and Xinjiang regions presents the characteristics of “self-sufficiency” application. Most of the coal gangue is composed of sandstone, clay rock, and aluminous rock, and its physical and chemical properties have multiple utilization potential. However, the comprehensive utilization method lacks systematic, compound, and leading scientific utilization methods. In this regard, a combination of cascade recovery of coal gangue is proposed. Three suggestions are proposed: resource utilization, source reduction mining, and mineralized CO2 negative carbon filling. The research results have important guiding significance for China Coal to optimize the layout of the coal industry, promote the high-value utilization of coal gangue, protect the ecological environment of the Kuangqu, and implement the “double carbon” goal.